Hand hygiene implementation: an easy step to improve public health - Fankhauser-Rodriguez, Carolina; Guitart, Chloé; Pittet, Didier (International Journal of Infection Control, 2020)
The World Health Organization has declared 2020 the “Year of the Nurse and Midwife”. On May 5th of this year, for the annual celebration of the SAVE LIVES: Clean Your Hands campaign, the WHO highlighted the critical role of nurses and midwives in promoting public health. Increasing well-trained nurse staffing will enable nurses and midwives to improve quality of care and prevent infections. The implications for improved nursing and health policy are many. Investing in nurses ensures better care for patients, reduces infections and the economic burden of healthcare-associated infections on countries' economies.